Organizacije za održavanje zrakoplova prema JAR-u 145 - Smrečki, Boris (Promet - Traffic&Transportation, 2012)
The paper deals with the issues of aircraft maintenance management per JAR 145. The introduction of JAR 145 has set the requirement for European airlines to adjust to the new system of maintenance and issuance of certificates on completed servicing as required by the Joint Airworthiness Requirements. From JAR 145 standards originate the requirements for personnel and equipment in compliance with ISO 9002, management aspects and types of servicing.